1979
DOI: 10.1677/joe.0.0830183
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin Inhibits Spontaneous and Prostaglandin-Driven Myometrial Activity in Anaesthetized Rats

Abstract: Porcine relaxin (250 guinea-pig units/mg) infused intravenously into anaesthetized rats at 20 micrograms/h reversibly abolished spontaneous intra-uterine pressure cycles yet left the myometrium responsive to oxytocin in doses of 4--8 mu. The inhibition was found to be primarily of the frequency, rather than of the amplitude, of pressure cycles. Relaxin (5 or 10 micrograms) was capable of completely suppressing uterine activity driven by prostaglandin F2 alpha infusion in oestrogen-treated ovariectomized rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
25
3

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 0 publications
4
25
3
Order By: Relevance
“…The ability of rat relaxin to inhibit myometrial activity in vivo and in vitro, and to soften the uterine cervix is consistent with the reports of McMurtry, Kwok & Bryant-Greenwood (1978), Mercado-Simmen, Bryant-Greenwood & Greenwood (1980) and Cheah & Sherwood (1980) that these tissues possess receptors for relaxin as evidenced by their binding of 12SI-labelled relaxin. These findings support the suggestion (Porter, 1979b) (Porter, Downing & Bradshaw, 1979). The finding that the rate of rise of intrauterine pressure was significantly elevated after treatment suggests that relaxin improves myometrial co-ordination.…”
Section: Discussionsupporting
confidence: 87%
“…The ability of rat relaxin to inhibit myometrial activity in vivo and in vitro, and to soften the uterine cervix is consistent with the reports of McMurtry, Kwok & Bryant-Greenwood (1978), Mercado-Simmen, Bryant-Greenwood & Greenwood (1980) and Cheah & Sherwood (1980) that these tissues possess receptors for relaxin as evidenced by their binding of 12SI-labelled relaxin. These findings support the suggestion (Porter, 1979b) (Porter, Downing & Bradshaw, 1979). The finding that the rate of rise of intrauterine pressure was significantly elevated after treatment suggests that relaxin improves myometrial co-ordination.…”
Section: Discussionsupporting
confidence: 87%
“…In addition to its classical actions on cervical ripening, uterine contraction, and pubic symphysis elongation (1,2), relaxin has been suggested to participate in the regulation of blood pressure (3)(4)(5)(6)(7)(8) and neuropeptide release, notably oxytocin and vasopressin (9)(10)(11)(12)(13). However, the results from these studies were conflicting, and the site of action of relaxin was undetermined.…”
mentioning
confidence: 99%
“…Miller et al (4) first reported that injection of an extract of pregnant sow ovary caused a transient fall in blood pressure when injected into anaesthetized dogs. In contrast, injection of up to 50 pg purified porcine relaxin in anaesthetized rats did not affect blood pressure (5). Preliminary experiments reported by Jones and Summerlee (6) indicated that acute iv injections of a standard dose of relaxin caused a rise in blood pressure and the release of vasopressin.…”
mentioning
confidence: 92%